1999
DOI: 10.1159/000012061
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks Applied to Survival Prediction in Breast Cancer

Abstract: In this study, we evaluated the accuracy of a neural network in predicting 5-, 10- and 15-year breast-cancer-specific survival. A series of 951 breast cancer patients was divided into a training set of 651 and a validation set of 300 patients. Eight variables were entered as input to the network: tumor size, axillary nodal status, histological type, mitotic count, nuclear pleomorphism, tubule formation, tumor necrosis and age. The area under the ROC curve (AUC) was used as a measure of accuracy of the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 24 publications
0
74
0
2
Order By: Relevance
“…Otherwise, the weights are adjusted to reduce this difference. In the present paper, the ANN model was constructed with a commercially available computer program (NeuralWare) using a modified cascade method together with an adaptive gradient learning rule (Lundin et al, 1999). The cascade mode of construction involves adding hidden nodes, one or more than one at a time, and always connecting all the previous nodes to the current node.…”
Section: Development Of Artificial Neural Network Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, the weights are adjusted to reduce this difference. In the present paper, the ANN model was constructed with a commercially available computer program (NeuralWare) using a modified cascade method together with an adaptive gradient learning rule (Lundin et al, 1999). The cascade mode of construction involves adding hidden nodes, one or more than one at a time, and always connecting all the previous nodes to the current node.…”
Section: Development Of Artificial Neural Network Modelmentioning
confidence: 99%
“…It should be mentioned that there is no strict rule to decide the ratio of training and test cases. A survey of the ANN literature found that the ratios 1 : 1 (Chattopadhyay and Chattopadhyay, 2008a), 7 : 3 (Lundin et al, 1999) and 3 : 1 (Perez et al, 2000) are frequently used in ANN applications. In the present paper an approach similar to that of Lundin et al (1999) has been adopted after examining the other approaches.…”
Section: Development Of Artificial Neural Network Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Lundin et al used artificial neural network and logistic regression models to predict 5 , 10 , 15 year breast cancer survival 8 . Pendharkar et al used several data mining techniques for exploring patterns in breast cancer 9 .…”
Section: Literature Surveymentioning
confidence: 99%
“…In breast cancer, area under the ROC curve (AUC) can be used as a measurement of accuracy when evaluating survival rate estimates for 5, 10, and 15 years in patients (Lundin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%